2010
DOI: 10.1016/j.nuclphysb.2009.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The puzzle of apparent linear lattice artifacts in the 2d non-linear σ-model and Symanzik's solution

Abstract: Lattice artifacts in the 2d O(n) non-linear σ-model are expected to be of the form O(a 2 ), and hence it was (when first observed) disturbing that some quantities in the O(3) model with various actions show parametrically stronger cutoff dependence, apparently O(a), up to very large correlation lengths. In a previous letter [1] we described the solution to this puzzle. Based on the conventional framework of Symanzik's effective action, we showed that there are logarithmic corrections to the O(a 2 ) artifacts w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 31 publications
5
97
0
Order By: Relevance
“…This would contradict Symanzik's effective theory. However, as investigated in detail [59,60], the standard and the modified actions indeed have lattice artifacts of O(a 2 log 3 (a/L)), with large logarithmic corrections mimicking O(a) effects. In particular, Symanzik's theory correctly describes the observed lattice artifacts.…”
Section: A Topological Lattice Action Without Topological Charge Suppmentioning
confidence: 91%
See 3 more Smart Citations
“…This would contradict Symanzik's effective theory. However, as investigated in detail [59,60], the standard and the modified actions indeed have lattice artifacts of O(a 2 log 3 (a/L)), with large logarithmic corrections mimicking O(a) effects. In particular, Symanzik's theory correctly describes the observed lattice artifacts.…”
Section: A Topological Lattice Action Without Topological Charge Suppmentioning
confidence: 91%
“…The step scaling function is affected by lattice artifacts which -for some time -seemed not to be described by Symanzik's effective theory. Interestingly, a recent careful study of the lattice artifacts has shown that large logarithms arise, and that Symanzik's theory does describe the lattice artifacts correctly [59,60]. Hence, one may conclude that the continuum limit of the finite-volume mass gap m(L) is finally well understood.…”
Section: The 2-d O(3) Model In the Continuum And With The Standard Lamentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in contrast to what Symanzik improvement suggests, the cut-off effects in the 2-d O(3) model appeared to be O(a) instead of O(a 2 ) [17,18]. A careful analysis of this apparent contradiction verified the Symanzik O(a 2 ) prediction, but showed that easily accessible lattice spacings are affected by large logarithmic corrections, which mimic O(a) behavior [19,20]. Recently, different lattice actions have been studied with the goal to improve the cut-off effects [21].…”
Section: Jhep03(2016)116mentioning
confidence: 79%